Taking Responsibility for Children - Noggle, Robert, 1966-; Brennan, Samantha (Book collections on Project MUSE., 2007)
"What do we as a society, and as parents in particular, owe to our children? Each chapter in Taking Responsibility for Children offers part of an answer to that question. Although the contributors vary in the approaches they take and the conclusions they draw, each one explores some aspect of the moral obligations owed to children by their caregivers. Some focus primarily on the responsibilities of parents, while others focus on the role of society and government." "Taking Responsibility for Children will be of interest to philosophers, advocates for children's interests, and those interested in public policy, especially as it relates to children and families."--BOOK JACKET.